1997
DOI: 10.1128/mcb.17.2.963
|View full text |Cite
|
Sign up to set email alerts
|

AP-1-Mediated Invasion Requires Increased Expression of the Hyaluronan Receptor CD44

Abstract: Fibroblasts transformed by Fos oncogenes display increased expression of a number of genes implicated in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
146
0
2

Year Published

1999
1999
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(153 citation statements)
references
References 69 publications
(84 reference statements)
5
146
0
2
Order By: Relevance
“…Cell surface CD44 is the receptor for hyaluronate, a major glycosaminoglycan component of the cellular matrix, and may promote tumor invasion (22). Adhesion to the cellular matrix, a critical step in the metastatic process, has been found to be CD44-dependent in several malignancies (23,24). Expression of 15-PGDH in A549 cells appeared to cause down-regulation of CD44.…”
Section: -Pgdh Is a Tumor Suppressormentioning
confidence: 99%
“…Cell surface CD44 is the receptor for hyaluronate, a major glycosaminoglycan component of the cellular matrix, and may promote tumor invasion (22). Adhesion to the cellular matrix, a critical step in the metastatic process, has been found to be CD44-dependent in several malignancies (23,24). Expression of 15-PGDH in A549 cells appeared to cause down-regulation of CD44.…”
Section: -Pgdh Is a Tumor Suppressormentioning
confidence: 99%
“…All of the CD44 variants (CD44v) contain insertions of various combinations of variant exons (1-10) located between exons 5 and 16 of the CD44 gene (Screaton et al, 1992(Screaton et al, , 1993. In contrast to merlin, which displays tumor-suppressor activity, CD44 promotes tumor invasion and metastasis (Gunthert et al, 1991;Sherman et al, 1994;Lamb et al, 1997;Yu et al, 1997;Stamenkovic, 1999, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…AP-1 is a heterodimeric protein composed of various combinations of the Jun and Fos family proteins, and this¯exibility permits transactivation or transrepression of gene expression (Bushel et al, 1995;De Cesare et al, 1995;reviewed in Karin et al, 1997). Upon transformation of 208F cells with v-fos, the cells show extensive reorganization in their cytoskeleton and become invasive (Hennigan et al, 1994;Lamb et al, 1997a). These cytoskeletal rearrangments result in a striking change in the morphology of the cells: they change from being¯at with F-actin stress ®bres to being bipolar with long pseudopodia, which are lined with cortical F-actin cables that have dynamic actin-rich membrane ru e-like structures at their tips.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that AP-1 is essential for invasion of FBR cells and 208F cells treated with EGF (Hennigan et al, 1994;Lamb et al, 1997a). This was achieved using antisense oligonucleotides to c-jun, and the expression of a c-Jun dominant negative mutant (TAM-67) to inhibit invasion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation